Conditions influencing the adoption of effective anti-deforestation policies in South America's commodity frontiers. (March 2017) - Nolte, Christoph; le Polain de Waroux, Yann; Munger, Jacob; Reis, Tiago N.P.; Lambin, Eric F.
Highlights: Reducing large-scale deforestation requires effective forest conservation policies. Adoption of such policies varied among South America's main deforestation frontiers. We study conditions associated with new anti-deforestation policies in 6 frontiers. Agricultural and environmental interests, tenure, and compliance affect adoption. Incentivizing new anti-deforestation policies might be difficult in many frontiers. Abstract: Reducing large-scale deforestation in commodity frontiers remains a key challenge for climate change mitigation and the conservation of biodiversity. Public and private anti-deforestation policies have been shown to effectively reduce forest loss, but the conditions under which such policies get adopted are rarely examined. Here we propose a set of conditions that we expect to be associated with the adoption of effective anti-deforestation policies in commodity frontiers. We then examine whether these conditions have influenced policy adoption in South America's major soy-and-cattle frontiers: the Brazilian Amazon, the Cerrado, the Chaco, the Chiquitano, and Paraguay's Atlantic Forest. By collating empirical data from diverse sources, including literature review, extensive expert interviews, and analysis of primary and secondary data, we show that the Cerrado, the Chaco, and the Chiquitano differ from the Brazilian Amazon in multiple ways that might have inhibited adoptions of effective anti-deforestation instruments. These conditions include: a higher importance of the agricultural sector within the respective countries, lower carbon stocks and species richness, higher prevalence of private land tenure, and higher baseline compliance with forest reserve regulations on private lands. We also observe that the adoption of the most effective private anti-deforestation instrument, commodity moratoria, may respond to similar conditions as those influencing the adoption of public instruments. Incentivizing public and private actors to adopt effective anti-deforestation policies in the Cerrado, Chaco, and the Chiquitano will likely be more challenging than it has been in the Brazilian Amazon.